2014
DOI: 10.1016/j.joen.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of Traumatized Immature Permanent Necrotic Teeth after Revascularization/Revitalization Therapy

Abstract: Introduction Revascularization treatment is rapidly becoming an accepted alternative for the management of endodontic pathology in immature permanent teeth with necrotic dental pulps. However, the success and timing of clinical resolution of symptoms and of radiographic outcomes of interest, such as continued hard tissue deposition within the root, are largely unknown. Methods In this prospective cohort study, 20 teeth were treated with a standardized revascularization treatment protocol, and monitored for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
116
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(137 citation statements)
references
References 22 publications
(25 reference statements)
12
116
1
8
Order By: Relevance
“…Regenerative endodontic therapy (RET) has become a viable alternative in the treatment of immature teeth with pulpal necrosis as long as an adequate disinfection of the root canal system is guaranteed 2) . Most of RET clinical reports have used either triple antibiotic paste (TAP) [3][4][5][6][7] or pure calcium hydroxide (Ca(OH)2) paste [8][9][10][11] , as intracanal medicaments for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regenerative endodontic therapy (RET) has become a viable alternative in the treatment of immature teeth with pulpal necrosis as long as an adequate disinfection of the root canal system is guaranteed 2) . Most of RET clinical reports have used either triple antibiotic paste (TAP) [3][4][5][6][7] or pure calcium hydroxide (Ca(OH)2) paste [8][9][10][11] , as intracanal medicaments for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it may induce an uncontrolled calcification of the canal space that would prevent the ingrowth of soft tissue with an odontogenic potential 9) . TAP consisting of metronidazole, ciprofloxacin and minocycline, has been successfully used to disinfect the canals in RET, achieving closure of the apex and thickening of the dentinal walls [3][4][5][6][7] . A potential disadvantage when using TAP is the possibility of tooth discoloration 4,12,13) due to minocycline 4,13) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several case reports and case series have shown clinically successful outcomes and further root development after regenerative endodontic treatment (5,6). Recent case reports and clinical studies have shown that root development as a possible indicator of pulp regeneration is not a predictable outcome (7)(8)(9). Among all aspects of root development (ie, increase in length, increase in root wall thickness, and apical closure), apical closure has been shown to be the most frequent finding (7), which could be unrelated to pulp regeneration (9).…”
mentioning
confidence: 99%
“…Recent case reports and clinical studies have shown that root development as a possible indicator of pulp regeneration is not a predictable outcome (7)(8)(9). Among all aspects of root development (ie, increase in length, increase in root wall thickness, and apical closure), apical closure has been shown to be the most frequent finding (7), which could be unrelated to pulp regeneration (9). Hence, histologic analysis of tissues formed inside the root canal after regenerative treatment is important, especially regarding the differentiation of stem cells into odontoblasts.…”
mentioning
confidence: 99%